Diversity of potassium solving microbes on andisol soil affected by the eruption of Mount Sinabung, North Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sembiring M, Sabrina T. 2022. Diversity of potassium solving microbes on andisol soil affected by the eruption of Mount Sinabung, North Sumatra, Indonesia. Biodiversitas 23: 1759-1764. Potassium (K) is one of the macronutrients needed by plants for seeds' growth, development, and quality. Andisols covered by volcanic ash from Mount Sinabung contain potassium ranging from 0.39-0.58 me/100g. The use of microbes is one of the alternatives methods to increase the availability of potassium in the soil that can be absorbed by plants. This study aimed to find environment-specific superior potassium-solvent microbes. Soil sampling was carried out in Kutarayat Village, Nama Teran Sub-district, Karo District, North Sumatra, Indonesia. The method used is random composite sampling by taking samples from 4 different locations. Sampling points were taken on Andisol soil that had been processed, covered with thin, medium, and thick ash. Sampling was carried out at a depth of 0-20 cm from the ground surface around the rhizosphere area. Isolation of bacteria and fungi was carried out by using multilevel dilutions. The microbes obtained after using the pour plate method were identified at molecular level by using PCR. Microbial potential test was carried out by using andisol soil which was incubated for 30 days. Parameters observed were soil pH, exchangeable potassium, soil organic carbon, and microbial population. 7 bacterial isolates and 3 potassium solubilizing fungi were isolated and identified during the present study. All bacterial and fungal isolates obtained were able to increase the availability of potassium soil exchange. The research results show that Talaromyces pinophilus can increase potassium soil exchange up to 102.94%.
Keywords: Andisol, microbial potential, potassium exchange, potassium solubilizing microbes, Talaromyces pinophilus